2006
DOI: 10.5713/ajas.2006.1784
|View full text |Cite
|
Sign up to set email alerts
|

Phytobiotics and Organic Acids As Potential Alternatives to the Use of Antibiotics in Nursery Pig Diets

Abstract: Two experiments were conducted to determine the effect of phytobiotics and organic acids on growth performance of nursery pigs as an alternative to antibiotics. Phytobiotics refer bioactive compounds from plant materials including essential oils and herbal extracts. In Exp. 1, 144 pigs, weaned at 23.4±0.3 d age, were allotted to three dietary treatments. Treatment diets were: 1) NC (no antibiotics and no phytobiotics); 2) PC (NC+carbadox, 50 mg/kg); and 3) PB (NC+phytobiotics; 0.1% PEP1000-1 ® ). Each treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 33 publications
1
43
0
3
Order By: Relevance
“…Most of the studies suggested that supplementation of plant extracts and essential oil blends does not improve performance of weaning pigs, regardless of whether carvacrol or thymol is contained or not (Namkung et al, 2004;Cho et al, 2006;Kommera et al, 2006;Manzanilla et al, 2006;Nofrarias et al, 2006). For example, the dietary supplementation with the plant extract containing 5% (w/w) carvacrol, 3% cinnamaldehyde and 2% capsicum oleoresin at dose of 300 mg/kg does not affect the performance of weaning pigs Nofrarias et al, 2006).…”
Section: Figure 1 Population Of Enterococcus Genus (A) Escherichia Cmentioning
confidence: 99%
“…Most of the studies suggested that supplementation of plant extracts and essential oil blends does not improve performance of weaning pigs, regardless of whether carvacrol or thymol is contained or not (Namkung et al, 2004;Cho et al, 2006;Kommera et al, 2006;Manzanilla et al, 2006;Nofrarias et al, 2006). For example, the dietary supplementation with the plant extract containing 5% (w/w) carvacrol, 3% cinnamaldehyde and 2% capsicum oleoresin at dose of 300 mg/kg does not affect the performance of weaning pigs Nofrarias et al, 2006).…”
Section: Figure 1 Population Of Enterococcus Genus (A) Escherichia Cmentioning
confidence: 99%
“…9 Another possible mechanism by which a probiotic may exert its benefi cial effect is through its effect on the permeability of the gut, which may increase nutrient uptake and thus improve growth performance. Unfortunately, research results have failed to consistently demonstrate benefi cial effects.…”
Section: What Are Probiotics?mentioning
confidence: 99%
“…Unfortunately, research results have failed to consistently demonstrate benefi cial effects. [9][10][11] What are synbiotics?…”
Section: What Are Probiotics?mentioning
confidence: 99%
“…Mixtures of essential oils based on thymol and carvacrol whose major sources are thyme and oregano, respectively (Burt, 2004), seem promising due to their antimicrobial (Kim et al, 1995;Cosentino et al, 1999;Baydar et al, 2004) and potential immunomodulatory properties (Woollard et al, 2007). A plant extract containing 6% of carvacrol and 0.14% of thymol, incorporated at 0.05% to 0.15% in a pig diet, had no effect on the plasma levels of the acute phase proteins, haptoglobin and C-reactive protein (Muhl and Liebert, 2007) and the inclusion of a commercial plant product composed of oregano oil mixed with anis and citrus oils did not improve the health status of piglets (Kommera et al, 2006). In contrast, an extract of Origanum vulgare, enriched with both thymol and carvacrol in similar proportions, was reported to protect low-weight growingfinishing pigs from disease (Walter and Bilkei, 2004).…”
Section: Plant Extractsmentioning
confidence: 99%